Poverty Alleviation Through Education: China’s Concrete Actions, Historical Achievements and Successful Experiences - Cheng, Xiongqing (Journal of Educational Research and Policies, 2024)
Poverty has been a global challenge since ancient times, which has seriously hindered the process of modernization and the cause of fairness in the world. Education is widely regarded as an effective tool to eliminate poverty, so in recent years, countries have paid special attention to education poverty alleviation. China has taken a number of practical and effective measures in education poverty alleviation. Through these efforts, China has made four historic achievements in education poverty alleviation: first, it has realized the comprehensive popularization and consolidation of compulsory education in poor areas, and completely solved the problem of "learning"; second, the linkage between education poverty alleviation and vocational education, the establishment of an effective mechanism to block the intergenerational transmission of poverty; third, the optimal allocation of educational resources, narrowing the gap between urban and rural areas and regions; the fourth is to establish a full-coverage precision funding system, eliminating the phenomenon of " out of school due to poverty " in education. These historic achievements are inseparable from adhering to the priority development of education and the organic coordination of the national system. China's specific actions, achievements and experience in the field of education poverty alleviation have contributed Chinese wisdom and Chinese programs to the cause of education poverty alleviation worldwide.